The Effectiveness of Sports Program among Typical Children and Children with Disabilities - Jafar, Amer Ali Mohamed; Khasawneh, Mohamad Ahmad Saleem (Journal of Ecohumanism, 2024)
This research aimed to introduce the effectiveness of sports programs for both typical children and children with disabilities that has garnered significant attention in recent years, highlighting the importance of inclusive physical activities in promoting health, social skills, and overall well-being. The main aim of this research is to show the importance of sports programs in general for both typical children and children with disabilities. The research presents a set of previous recent studies and research that relied on sports programs for both typical children and children with disabilities. The research ends with a set of recommendations, including the necessity of relying on practices that have been proven scientifically and practically effective in attending to sport programs for typical children and children with disabilities.